2011
DOI: 10.4489/myco.2011.39.1.026
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Effects of Silver Nanoparticles against Powdery Mildews on Cucumber and Pumpkin

Abstract: Powdery mildew is one of the most devastating diseases in cucurbits. Crop yield can decline as the disease severity increases. In this study, we evaluated the effect of silver nanoparticles against powdery mildew under different cultivation conditions in vitro and in vivo . Silver nanoparticles (WA-CV-WA13B) at various concentrations were applied before and after disease outbreak in plants to determine antifungal activities. In the field tests, the application of 100 ppm silver nanoparticles showed the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(93 citation statements)
references
References 10 publications
5
88
0
Order By: Relevance
“…ChNPs 20 ppm concentration was found less effective for inhibition of mycelial growth and spore germination. This respect with Lamsal et al [18] who reported that silver nanoparticles inhibited growth of Colletotrichum spp. With 50 ppm and 100 ppm by 84.56% and 93.5% respectively.…”
Section: Effect Of Chitosan and Silver Nps On Radial Growth Of B Fabsupporting
confidence: 66%
See 2 more Smart Citations
“…ChNPs 20 ppm concentration was found less effective for inhibition of mycelial growth and spore germination. This respect with Lamsal et al [18] who reported that silver nanoparticles inhibited growth of Colletotrichum spp. With 50 ppm and 100 ppm by 84.56% and 93.5% respectively.…”
Section: Effect Of Chitosan and Silver Nps On Radial Growth Of B Fabsupporting
confidence: 66%
“…While disease inhibition calculated in basis of the equation: the cells [18,36,37]. Other reports proposed that the mechanism of nanoparticles is related to their penetration into the fungal cell [38][39][40].…”
Section: Disease Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on the applicability of silver naoparticle for controlling plant diseases has been limited till date (Lamsal et al, 2011). Silver nanoparticles, which have a high surface area and high fraction of surface atoms, have high antimicrobial effect as compared to the bulk silver.…”
Section: Use Of Ag Nanoparticle For Better Plant Health Managementmentioning
confidence: 99%
“…Not much is known about the effects of silver on phytopathogenic fungi as most studies have focused on bacterial and viral pathogens of animals. The field study has suggested that, the efficacy of silver is greatly influenced by application time and preventive applications of silver nanoparticles work better before fungal inoculam penetrate and colonize the plant tissue (Lamsal et al, 2011). The study on antifungal activity of silver nanoparticles suggested that nanometer-sized silver possesses different properties, which might come from morphological and structural (Changes (Nel et al, 2003).…”
Section: Use Of Ag Nanoparticle For Better Plant Health Managementmentioning
confidence: 99%